Pattern of Prostate Specific Antigen and Gleason Score in Relation to Imunohistochemistry Features in Prostate Adenocarcinoma Patients in Dr. Hasan Sadikin General Hospital - Azela Glady; Endah Hamidah; Rahmat Budi Prasetyo; Agung Budi Sutiono (Faculty of Medicine Universitas Padjadjaran, 2016)
Objective: To review the correlation between prostate specific antigen (PSA) and Gleason score and Cav-1 for diagnosing prostate adenocarcinoma.Methods: Data were collected from one hundred fifty-nine patients with prostate adenocarcinoma at the Department of Urology, Dr. Hasan Sadikin General Hospital in the period of January 2008–December 2010. The PSA levels were measured and classified into <4 ng/ml, 4–10 ng/ml, and >10 ng/ml. The results were then analyzed and compared to the imunohistochemistry (caveolin-1) staining in the literature. The Gleason score was also noted and analyzed. Results: This study confirmed that positive caveolin-1 expression was related to the clinical markers of disease progression and was predictive of poor clinical outcome after surgery. The PSA results showed that one hundred fourty-one adenocarcinoma patients had a PSA level of >10 ng/ml with Gleason score of gleason 5–6 as the most common score. However, there was no correlation between PSA and Gleason score and caveolin-1 for diagnosing prostate adenocarcinoma.Conclusions: Caveolin-1 cannot be used to measure Gleason and PSA score due to different markers that have various advantages and disadvantages to predict carcinoma prostate. Therefore, further studies are needed. Keywords: Gleason score, imunohistochemistry, prostate adenocarcinoma, prostate specific antigen DOI: 10.15850/ijihs.v4n1.679